Xác định tính chất động học vủa đới đứt gãy ở khu vực Nam Trung Bộ bằng phần tích khe nứt kiến tạo - Hùng, Phạm Văn (Vietnam Journal of Earth Sciences, 2000)
Defining kinematic feature of the fault inSouthern Central part ofViet Namby analysing tectonic fractural distribution